Factors related with adherence to the rehabilitation treatment of type 2 diabetic patients who unde - Villegas Flores, Lourdes (2023)
Objective: To determine clinical and sociodemographic factors related to the adherence to rehabilitation treatment among type 2 diabetic patients who underwent lower limb amputation. Methods: An observational retrospective study that included 113 type 2 diabetic patients attended at the Departamento de Investigación, Docencia y Rehabilitación Integral en Amputados, quemados y Trastornos Posturales del Instituto Nacional de Rehabilitación “Dra. Adriana Rebaza Flores” AMISTAD PERÚ – JAPÓN from 2016 to 2019. Clinical and sociodemographic variables were collected; to measure adherence patients had to attend five evaluations and the discharge visit after a prosthetic device had been inserted. Results: 75.52% were males; mean age was 66.6 ± 12.1 years, and mean time after insertion of the prosthetic device was 11.4 ± 6.75 months. Factors associated with no adherence were age, socioeconomic level, marital status and health care coverage (p<0.05). Conclusions: Most of the type 2 diabetic patients who underwent lower limb amputation were males, adherence to the rehabilitation treatment was related to sociodemographic factors.